Efficacy and Safety of Oral Beclomethasone Dipropionate in Ulcerative Colitis: A Systematic Review and Meta-Analysis. - Francesco Manguso; Raffaele Bennato; Giovanni Lombardi; Elisabetta Riccio; Giuseppe Costantino; Walter Fries (PLoS ONE, 2016)
Background and aim We performed a systematic review and meta-analysis of all the available evidence comparing efficacy and safety of oral prolonged released beclomethasone dipropionate (BDP) to active oral controls in patients with mild-to-moderate ulcerative colitis (UC). A subgroup-analysis compared the effectiveness of BDP and 5-ASA. Methods Literature research was performed in different databases, as well as manual search to identify abstracts from international meetings with data not included in extensive publications. Experts in the field and companies involved in BDP development and manufacture were contacted to identify unpublished studies used for registration purposes. Dichotomous data were pooled to obtain odds ratio meta-analysis. Results Five randomized controlled trials that compared oral BDP 5mg/day vs. all oral active controls in treating UC were identified as eligible. Efficacy and safety have been addressed after 4-week treatment period. One study evaluated efficacy and safety of BDP vs. prednisone and 4 of BDP vs. 5-ASA. Treatment with oral BDP 5 mg/day induces a significant better clinical response compared to oral 5-ASA (OR 1.86, 95% CI = 1.23-2.82, P = 0.003). The effect is detectable even when the comparison to prednisone is added (OR 1.41, 95% CI = 1.03-1.93, P = 0.03). Data on remission indicate that the potential clinical efficacy of BDP may be better than 5-ASA (OR 1.55, 95% CI = 1.00-2.40, P = 0.05). This difference is lost when the comparison with prednisone is added (OR 1.30, 95% CI = 0.76-2.23, P = 0.34). The safety analysis showed no differences between BDP and 5-ASA (OR 0.55, 95% CI = 0.24-1.27, P = 0.16). The lack of difference is maintained even when the study with prednisone is added (OR 0.67, 95% CI = 0.44-1.01, P = 0.06). However, the trend of difference is clear and indicates a more favourable safety profile of BDP compared to 5-ASA and PD. Conclusions Oral prolonged release BDP showed a superior efficacy vs. oral 5-ASA in inducing clinical improvement of mild-to-moderate UC with a similar safety profile.